Studying how comparative data studies can contribute to macro social work: Insights from the Childcare Gap Policy Study Project. - Chau, Ruby Chui Man; Yu, Sam Wai Kam; Lo, Iris Po Yee; Yu, Clement Guo (International Social Work, 2026)
This article seeks to contribute to the advancement of macro social work with a focus on evidence-based transnational policy practices. It explores how comparative data research can support these practices. To illustrate this, a study on childcare gap policies is presented. This study examines how comparative data research can be used to influence the European Commission's policies on reducing childcare gaps within the European Union. This article responds to the calls for macro social workers to collaborate with other disciplines and utilize evidence to inform their practices.